Conductive films prepared from inks based on copper nanoparticles synthesized by transferred arc discharge. (10th October 2019) - Fu, Qingqing; Stein, Matthias; Li, Wen; Zheng, Jingzhi; Kruis, Frank Einar
Abstract: Copper nanoparticles (NPs) are considered as a promising alternative for silver and gold NPs in conductive inks for the application of printing electronics, since copper shows a high electrical conductivity but is significantly cheaper than silver and gold. In this study, copper NPs were synthesized in the gas phase by transferred arc discharge, which has demonstrated scale-up potential. Depending on the production parameters, copper NPs can be continuously synthesized at a production rate of 1.2–5.5 g h −1, while their Brunauer–Emmett–Teller sizes were maintained below 100 nm. To investigate the suitability in electronic printing, we use ball milling technique to produce copper conductive inks. The effect of ball milling parameters on ink stability was discussed. In addition, the electrical resistivity of copper films sintered at 300 °C in reducing atmosphere was measured to be 5.4 ± 0.6 μ Ω cm which is about three times higher than that of bulk copper (1.7 μ Ω cm). This indicates that conductive inks prepared from gas-phase synthesized copper NPs are competitive to the conductive inks prepared from chemically synthesized copper NPs.